2012
DOI: 10.1146/annurev-clinpsy-032511-143108
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Chronic Illness in Childhood and Adolescence

Abstract: Chronic illnesses and medical conditions present millions of children and adolescents with significant stress that is associated with risk for emotional and behavioral problems and interferes with adherence to treatment regimens. We review research on the role of child and adolescent coping with stress as an important feature of the process of adaptation to illness. Recent findings support a control-based model of coping that includes primary control or active coping (efforts to act on the source of stress or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
467
2
44

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 543 publications
(556 citation statements)
references
References 110 publications
24
467
2
44
Order By: Relevance
“…If shown to be generalizable/transferrable, interventions for these concerns could be implemented at local levels according to contextual needs. A feature of the most prominent needs is that they are difficult to eliminate or 'problem-solve' and may require more accommodative coping (secondary control versus primary control; e.g., [44]) -in this respect, they resemble prominent needs in chronic illness conditions (consistent with a broader shift in experiences of advanced cancer). There is a need now for interventional studies demonstrating that assessed 'unmet needs' can be addressed: evidence to date for the efficacy of interventions targeting unmet needs is weak [45] and questions remain with respect to whether this reflects limitations of needs assessment tools, broader methodological flaws, ineffectiveness of available interventions, or the inherent difficulty of 'meeting' some expressed needs.…”
Section: Resultsmentioning
confidence: 99%
“…If shown to be generalizable/transferrable, interventions for these concerns could be implemented at local levels according to contextual needs. A feature of the most prominent needs is that they are difficult to eliminate or 'problem-solve' and may require more accommodative coping (secondary control versus primary control; e.g., [44]) -in this respect, they resemble prominent needs in chronic illness conditions (consistent with a broader shift in experiences of advanced cancer). There is a need now for interventional studies demonstrating that assessed 'unmet needs' can be addressed: evidence to date for the efficacy of interventions targeting unmet needs is weak [45] and questions remain with respect to whether this reflects limitations of needs assessment tools, broader methodological flaws, ineffectiveness of available interventions, or the inherent difficulty of 'meeting' some expressed needs.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic illness, such as CFS, may be considered as a problem that cannot (yet) be cured or solved, and where an accommodative coping strategy and illness acceptance is to be preferred. In line with this view, cross-sectional studies indicate that acceptance plays a role in adjustment to chronic illnesses, amongst which CFS and that acceptance has been found to be associated with a better mental health-related quality of life (MQoL) [17,27,[29][30][31]. Of further interest are the results of Brooks and colleagues, who found that CBT for CFS resulted in an increase of acceptance, and that lack of acceptance was associated with fatigue and physical functioning [15].…”
Section: Introductionmentioning
confidence: 93%
“…This way of coping with adversity is more and more acknowledged to be related to a good adjustment to chronic illness [17][18][19][20][21][22]. Its function is also well-articulated in self-regulatory models of coping [23][24][25].One example of such a model is the 'Dual-Process Model of Coping of Brandtstädter and colleagues' [26][27], which distinguishes between two complementary coping strategies: accommodative coping and assimilative coping.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, acceptance, predicts better adjustment in both IBD (Voth & Sirois, 2009) and arthritis (Pinto-Gouveia, Costa, & Marôco, 2013). But, in the context of chronic illness distraction coping is not maladaptive as Allen and Leary (2010) suggest, but adaptive (Compas, Jaser, Dunn, & Rodriguez, 2012). For this reason it was not examined.…”
Section: Self-compassion and Coping With Chronic Illnessmentioning
confidence: 99%